Vernal keratoconjunctivitis and eosinophilic esophagitis: A rare combination? - Maria Cristina Artesani, MD; Sara Urbani, MD; Carla Riccardi, MD; Mariacristina Esposito, MD; Paola De Angelis, MD; Francesca Rea, MD; Renato Tambucci, MD; Monica Malamisura, MD; Luca Buzzonetti, MD; Alessandro Giovanni Fiocchi, MD (World Allergy Organization Journal, 2024)
Vernal keratoconjunctivitis (VKC) is a bilateral ocular inflammatory disease with a conjunctival and corneal involvement and typical onset during childhood. Eosinophilic esophagitis (EoE) is a chronic disease characterized by eosinophilic inflammation of the mucosa (≥15 eosinophils/HPF) and symptoms of esophageal dysfunction. EoE and VKC are both immune-mediated diseases sharing a similar pathogenetic mechanism and a high association with other allergic diseases. Nevertheless, no data are currently available about their clinical association. We present 4 cases of concomitant diagnosis of vernal keratoconjunctivitis and eosinophil esophagitis suggesting that these conditions may coexist in the same patient more frequently than expected. Health care providers should be aware of the possibility of co-occurrence in their daily practice.